The Influence of Slow Stroke Back Massage, Cold-compress and Warm-compress to the Level of Prostaglandin F2? (PGF2?) in Primary Dysmenorrhea - Mukhoirotin1, Kurniawati1, Diah Ayu Fatmawati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The cause of primary dysmenorrhea is excessive release of the hormone prostaglandin F2-alpha (PGF2?). The aim of this study was to assess the influence of SBBM, cold-compresses and warm-compresses toward the level of PGF2? in primary dysmenorrhea, using Post Test Only with Control Group Design and PretestPostest Control Group Design. The subjects were 76 female-student, selected by purposive sampling. NRS used to measure the pain level and ELISA used to measure PGF2? levels. The data were analyzed by using Paired Sample T-Test, One-Way Anova and Kruskal-Wallis test. SSBM, cold-compresses and warmcompresses are effective to decreasing of pain level and PGF2? levels in primary dysmenorrhoea.